STUDI ASPEK REPRODUKSI IKAN BAUNG (Mystus nemurus Cuvier Valenciennes) DI SUNGAI BINGAI KOTA BINJAI PROVINSI SUMATERA UTARA - Vindy Rilani Manurung; Yunasfi Djayus; Desrita Desrita (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2013)
Baung fish (Mystus nemurus CV) is a fish of high economic value. Thepurpose of research to reproductive aspects (sex ratio, gonad maturity level (TKG),gonad maturity index (IKG), first time size mature gonad, fecundity and eggdiameter). The study was conducted from March to May 2013 at three locations . Themethod used descriptive analytic .Sex ratio of Baung fish with unbalanced sex ratio with a value of 4.5>3.8.Gonad maturity level (TKG) found I- IV, while the male fish only I- III. gonadmaturity index (IKG) female fish 0.01-7.33% and 0.01-0.26% for male fish . The firstgonad size mature female fish is 268 mm . Fecundity of Baung fish is 18229-44 392eggs . Distribution diameter on the distribution of fish eggs female 0.38 to 2.05 mm.Keyword : Baung fish, Bingai river, Fish reproduction, Mystus nemurus CV.